Headache in children: update on biobehavioral treatments - Kropp, Peter; Meyer, Bianca; Landgraf, Mirjam; Ruscheweyh, Ruth; Ebinger, Friedrich; Straube, Andreas (Neuropediatrics, 2013)
Biobehavioral pain treatment consists of relaxation techniques, biofeedback treatment, operant pain treatment, pain coping, cognitive-behavioral treatment, and multimodal treatment. Especially in the treatment of pediatric headache, biobehavioral procedures have been found to be highly efficient and are widely accepted. They present similar effects as pharmaceutical treatments. In general, when standardized treatment programs are applied, the sessions are highly effective.